THE INFLUENCE OF INTENSITY OF GADGET USE AND LEARNING MOTIVATION ON PAI LEARNING OUTCOMES THROUGH MENTAL HEALTH AS A MEDIATOR FOR BOGOR MUHAMMADIYAH MIDDLE SCHOOL STUDENTS - Lucky Dewanti; Nurdini Ferianti; Heru Wardany (International Journal of Social Science, 2024)
This research aims to: (1) find out the significance of the influence of using gadgets as learning media on students' PAI learning outcomes (2) find out the significance of the influence of learning motivation on students' PAI learning outcomes (3) find out the significance of the influence of using gadgets as learning media and learning motivation on results learning PAI for class students. (4) the influence of mental health on the use of gadgets on learning motivation and PAI learning outcomes. Answering this question, this research was designed using a quantitative approach, where the data is in the form of numbers. The population in this study were 7th grade students, namely 160 children. To determine the sample size, researchers looked at the Morgan and Krecjie tables. So. According to the population size, the researcher took a sample of 160 students. The data collection instrument is by using questionnaires and documentation. Data analysis techniques use observation and tests. The analysis technique used is descriptive statistics using the SPSS computer program facilities. Based on data analysis, it was found that: (1) the use of gadgets as a learning medium had a significant effect on PAI learning outcomes in students' jurisprudence subjects, with a score of 0.008 p < 0.05 (2) learning motivation had a significant influence on PAI learning outcomes for grade 7 students, an estimated value of 0.030 with p <0.05 was obtained. (3) The use of gadgets as a learning medium for PAI learning outcomes with mental health as a mediator in grade 7 students was obtained an estimated value of 0.008 with p <0.05, (4) Mental health had a significant effect. on pie learning outcomes, an estimated value of 0.240 was obtained with a p value of 0.001 maa p <0.05